APLIKASI INPUT METHOD EDITOR (IME) JEPANG BERBASIS WEB - Alexander Setiawan; Rolly Intan; Rikko Filiano (JUTI: Jurnal Ilmiah Teknologi Informasi, 2010)
Japanese language uses thousands of characters for its writing system. A system called Input Method is used to enable the inputs of those characters using a standard keyboard. Some Input Method applications were already developed, from the desktop application to the web-based application. Unfortunately, those applications are not flawless. In this research, an application using the Input Method system has been developed to cover the weaknesses of those applications that already developed before. This Input Method application system uses standard web technology. Such as JavaScript on the client side. PHP on the server side. MeCab: Yet Another Part-of-Speech and Morphological Analyze dictionary is used for its dictionary. The core algorithm uses Longest Match Method for word searching.